Implementation of Student Learning Independence in Ethnoscience-Oriented Force Topics Through Problem Based Learning (PBL) Learning Model - Elsa Wahyuni; Yanti Fitria; Solfema; Abna Hidayati (Jurnal Penelitian Pendidikan IPA, 2023)
This research is motivated by the low independence of science learning of elementary school students. This research aims to determine the effect of the application of the Ethnoscience-Oriented Problem Based Learning (PBL) model on the learning independence of students in class IV Elementary School. The type of research used is Quasi Experimental. The study population was grade IV elementary school students in Â Gugus IV Padang City T.A 2023/2024. The sampling technique used was simple random sampling obtained at SDN 28 Padang Sarai in class IVB as the experimental class and class IVA as the control class. The instrument used in this research is a questionnaire instrument. Questionnaires are used to measure student learning independence in science learning for grade IV elementary school students. The data analysis technique in this study used an independent sample t test, Based on the results of the study, the results obtained: The significance value of 0.000 < 0.05, then in accordance with the basis for decision making, it is found that H0 is rejected and Ha is accepted, which means that the learning independence of students in science learning is significantly high which is taught with the PBL Ethnoscience-Oriented learning model compared to conventional learning.